2015
DOI: 10.4028/www.scientific.net/jera.19.103
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Bionic Technology for Drag Reduction Based on Analysis of Abilities the Earthworm

Abstract: The earthworm is a common terrestrial animal, its physical structure and morphology characteristics are very distinctive. Through of imitation of the special abilities of earthworms, people can get the material to research on bionic technology, such as the jet, non-smooth surface, etc. It can provide the new design ideas for engineering technology. The study of earthworm body structure and its movement mechanism, can help people to find the drag reduction method in the process of movement. In addition, the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Crawling speed varies both within and among individuals. The crawling speed of earthworms on wet ground is about 5 mm·s –1 ( Gu et al, 2016 ), and the drier the place, the slower the crawling speed. Generally, the ratio of the static diameter/length of earthworm segment is greater than 1, rendering each segment a discus-like shape.…”
Section: Biological Characteristics Of Earthworms and Related Robots ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Crawling speed varies both within and among individuals. The crawling speed of earthworms on wet ground is about 5 mm·s –1 ( Gu et al, 2016 ), and the drier the place, the slower the crawling speed. Generally, the ratio of the static diameter/length of earthworm segment is greater than 1, rendering each segment a discus-like shape.…”
Section: Biological Characteristics Of Earthworms and Related Robots ...mentioning
confidence: 99%
“…Currently, there are several reviews that mention earthworm-inspired soft robots in their descriptions in the field of engineering application ( Dario and Mosse, 2003 ; Kheirikhah et al, 2011 ; Kim et al, 2013 ; Gu et al, 2016 ; Wei et al, 2021 ; Dong et al, 2022 ) and robotic gastroscopes ( Marlicz et al, 2020 ; Manfredi, 2021 ). But detailed classification, actuation analysis and discussion of such robots are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown that the dorsal pores of earthworm are opened under the stimulation of alcohol and spray body fluid up to 20 cm in height [19]. ere are regular pits on the surface of earthworm to secrete body fluid, which makes earthworm have a unique self-lubrication mechanism [20].…”
Section: Design and Processingmentioning
confidence: 99%
“…Natural organisms have evolved excellent functions and unique geometric structures over billions of years, and among them, animals that are good at digging have evolved superior digging organs. These superior characteristics have been applied to the field of resistance reduction in agricultural machinery, and fruitful research results have been achieved [30,31]. Li et al [32,33] studied the structural characteristics of the dung beetle's touching soil body surface and designed a convex bun type bionic plow, acquiring the efficiency of drag reduction 6.6% to 12.7% through soil bin tests.…”
Section: Introductionmentioning
confidence: 99%